Some aspects of the purification efficiency of Phragmites australis in a root zone system - Németh, Nóra; Lakner, Gábor (Acta Biologica Szegediensis, 2002)
Today natural wastewater treatment technologies gain more importance. Root zone systems are real alternatives for the purification of the sewage of smaller settlements. Focusing on the importance of the role of the plant in these systems we tried to learn more about these systems. This paper compares the differences of the element- and nutrientelimination efficiency of the gravel and the reed beds of the system in Szügy and gives some observations concerning the element- and nutrient-accumulation of the different parts of the reed (Phragmites australis). Our results indicate the annual differences between the two treatments and those of the accumulation of the reed. The reed beds prove to function better in removing phosphorus, NH4-N and most of the metals.